1996
DOI: 10.1038/bjc.1996.600
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polypeptide expression in benign and malignant human breast lesions: down-regulation of cytokeratins

Abstract: Summary Malignant progression of tumour cells is caused by the accumulation of genetic defects, which when combined will generate a large phenotypic diversity. Simultaneous quantitation of a large number of gene products in tumour cells is desirable, but difficult to achieve. We have here quantitated the levels of a number of abundant polypeptides in human breast carcinoma cells using two-dimensional gel electrophoresis (2-DE; PDQUEST). For this purpose, tumour cells were prepared from the tissue of 17 breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 19 publications
3
58
0
2
Order By: Relevance
“…Studies from ovarian carcinoma have shown large heterogeneity between pairs of different ovarian carcinomas with a correlation coefficient of 0.54 (Alaiya et al, 1999). Studies of breast carcinoma have likewise shown large intertumoural heterogeneity, with a correlation coefficient of 0.57 for diploid tumours and 0.48 for aneuploid tumour (Franzen et al, 1996). Consequently, pairs of vaginal and cervical carcinomas seem to be more homogeneous than pairs of ovarian and breast carcinomas.…”
Section: Discussionmentioning
confidence: 92%
“…Studies from ovarian carcinoma have shown large heterogeneity between pairs of different ovarian carcinomas with a correlation coefficient of 0.54 (Alaiya et al, 1999). Studies of breast carcinoma have likewise shown large intertumoural heterogeneity, with a correlation coefficient of 0.57 for diploid tumours and 0.48 for aneuploid tumour (Franzen et al, 1996). Consequently, pairs of vaginal and cervical carcinomas seem to be more homogeneous than pairs of ovarian and breast carcinomas.…”
Section: Discussionmentioning
confidence: 92%
“…Accumulation of CALR protein is observed in a few cancers, including breast cancer (Franzen et al, 1996) and hepatocellular carcinoma (Yoon et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…8 Immunostaining for keratin 15 is demonstrated as a useful method for the differential diagnosis between basal cell carcinoma and trichoepithelioma. 9,10 Normal epithelial cells undergo apoptosis if they lose cell-cell or cell-matrix contact, a process which has been termed anoikis. 11 ± 13 This anchorage-dependent apoptosis prevents detached epithelial cells from colonizing at inappropriate sites, and is thus essential for maintaining intact tissue organization.…”
Section: Introductionmentioning
confidence: 99%